Static Strength of Elliptical Chords T-Tubular Joints Subjected to Mechanical Loading - Hamed, Abdalla F. (1999)
T-Tubular joints of elliptical and circular cross-section tubes for the main tube (chord) with circular cross-section tubes for the braces have been studied. Experimental tests for the joint strength of these welded T-joints under tension, compression, in plane bending and out of plane bending have been carried out. A rig has been designed and built for that purpose. Three cases of T-joint connections were selected. For Case 1, the brace was perpendicular to the circular chord outer diameter. For Case 2, the brace was perpendicular to elliptical chord minor diameter and for Case 3, the brace was perpendicular to elliptical chord major diameter. The chord was held as fixed-fixed for all cases. The material used for all tubes was mild steel. The ultimate loads and ultimate moments obtained from the tests are converted to non-dimensional strengths throughout this investigation. This was done to make efficient comparisons. Finite element models for similar T -joints have been developed and used to analyze the effect of axial loading and bending moment. Tension, compression, in plane bending and out-of-plane bending load modes were studied. A comparison between experimental results and finite element analysis was also carried out. Another comparison between experimental results and existing empirical equation results for similar circular chords tubular joints was also carried out. The results extracted from this study for tension, compression, in-plane bending and out-of-plane bending modes for the ultimate loads and moments of Case 1, are 53.85 kN, 25.43 kN, 0.76 kN.m and 0.40 kN.m respectively. On the other hand, the results for Case 2 of the ultimate loads and moments are 42.48 kN, 1 8.39 kN, 0.63 kN.m and 0.37 kN.m respectively. While for Case 3 the ultimate loads and moments are 64.86 kN, 28.95 kN, 1.00 kN.m and 0.55 kN.m respectively. The results obtained show that for axial tension and compression loading modes, Case 3 increases by 17.0% and 12.2% respectively when compared to Case 1 while 24.0% and 27.3% increase were found for in-plane and out-of-plane bending load modes respectively. This shows a significant improvement in the static strength for elliptical chords tubular joints (Case 3) under different loading modes when compared to circular chords tubular joints (Case 1).